Talent Management and Teacher Leadership Talent Development in High Performing School in Malaysia - Mohd Hamzah, Mohd Izham; Shamsudin, Shuhaida (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2017)
Researches on the effective leadership reveal that principals in high performing schools are successful in improving schools outcomes through who they are, the strategies they use, as well as the specific combination and timely implementation and management of these strategies as a result of the unique contexts in which they work. The present research work tries to explore and confirm the talent management factors (TMFs) responsible for developing teacher leadership talent (TLT). The proposed TMFs were tested and validated through a sample of 400 teachers of High Performing School in Malaysia using Amos 19. Hypotheses were tested at a 95% confidence level and the Root Mean Square Error of Approximation (RMSEA), Tucker-Lewis Index (TLI) and Comparative Fit Index (CFI) were used to test the structural equation model of talent management. The obtained RMSEA value was 0.049, TLI value was 0.942 and CFI value was 0.962 which indicated a good model fit and appropriateness. Analysis of the results demonstrated that the level of implementation of talent management falls into the range of being very good and has a significant relationship with a teacher leadership talent development of the organization in the studied population. This study is one of very few studies to provide an integrative perspective of TMFs for developing TLT in high performing school; it adds to the extremely limited number of empirical studies that have been conducted to investigate talent management in the education sector and how teacher leaders start as individual contributors and move up into management and leadership roles.